E-016 Low cost, efficient, highly effective method for therapeutic arterial occlusion of the internal carotid or vertebral artery with flow control. (4th July 2012) - Heck, D
Abstract : Therapeutic internal carotid or vertebral artery occlusion is occasionally recommended for a variety of cerebrovascular diseases, including giant aneurysms, vessel ruptures, and arteriovenous fistulae. With the removal of detachable balloons from the U.S. market, there is no ideal device to occlude a cerebral vessel rapidly and safely. Intracranial occlusion of cerebral vessels presents challenges of vessel tortuosity, and the possibility of cerebral embolization during the process of occluding the artery. Coils designed for endovascular occlusion of brain aneurysms are often used because they are deliverable in the intracranial circulation. However, these products are not highly effective for this application, expensive, and multiple coils are often needed which leads to a high cost procedure. Further, if no flow control is used during the procedure, the potential for cerebral embolization is real as thrombus begins to form at the site of occlusion. When proximal balloon occlusion is used, there is no way to "test" the occlusion short of deflating the balloon. Here presented are two cases, one in the internal carotid artery and one in the vertebral artery, of therapeutic occlusion using balloon occlusion guide catheters for flow arrest in the internal carotid artery, and flow reversal in the vertebral artery. The first patient is a 49 year old who presented with acute pain and cranial nerve III palsy and a giant right cavernous carotid aneurysm, and the second a 69 year old who presented with hearing loss and balance difficulty and a giant dissecting aneurysm of the left vertebral artery. Intracranial occlusion was achieved in each case with Interlock coils (Boston Scientific), a 0.018″ fibered, detachable coil, and then the vessel occluded proximally with an Amplatzer vascular plug (St. Jude Medical) to ensure cessation of flow prior to occlusion balloon deflation. The total cost of embolics in each case was <3000 dollars. The principles outlined are generalizable to a variety of situations where parent vessel occlusion is the desired treatment. Competing interests: None.